(3GdYbjOI GdeQGcTjIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3Ydi Hf MSf Hf eMeO GdMQGfi s)
(3ChdgG (B:s
(3eSCdI SFd YfgG SjOfG hgj eSCdI TQjaI GTJedJ Ydi ZQQ ef GdebGUO GdegeI eY UZQgG SCd YfgG GdTjN eMeO Hf eMeO GdeQGcTi ai TghQ SfI GKfJi YTQ hSHYeGFI GdMeO ddg QH GdYGdejf jLH Ydi cd GdNdGFb GdEbQGQ HeG LGA Hg Yf GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hgPg cdgG fUhU Jfai Cf Jchf UaGJgq s
(3Vef eLehY , JQJjHgG (B: 5s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds